In vitro screening of anti-methanogenic additives for use in Australian grazing systems - Parra, Mariano C.; Forwood, Daniel L.; Chaves, Alex V.; Meale, Sarah J. (Frontiers in Animal Science, 2023)
Despite considerable effort to develop and optimise additives to reduce methane emissions from cattle, little information on additive effectiveness exists for cattle under grazing scenarios. As the majority of Australian cattle production occurs on grazing land it is pertinent to report on the use of additives under simulated conditions. The current study evaluated the addition of nine additives to Rhodes grass hay under in vitro conditions, to estimate their impact on methane (CH4), gas production, and rumen fermentation parameters (volatile fatty acids, rumen pH and in vitro dry matter digestibility [IVDMD]). Citral extract at 0.1% of rumen media decreased all CH4 production parameters, but reduced gas production and digestibility, compared to a 100% hay control. Similarly, Sandalwood essential oil decreased CH4 production at 48 h, IVDMD and gas production, compared to the control. Biochar+nitrates at 5 and 8% DM, and Biochar +Asparagopsis at 5% DM decreased cumulative CH4 production (15.6%, 25.9%, 23.8%, respectively ; P < 0.01), compared to the control. No changes in IVDMD and gas production were observed. As such, the biochar additives were considered the most promising additives from those evaluated with a substrate designed to replicate Australian grazing systems.